The Gehring Lemma: Dimension free estimates. (December 2018) - Kristensen, Jan; Stroffolini, Bianca
Abstract: We present a dimension free estimate for the exponent of higher integrability in Gehring's Lemma for an inhomogeneous weak reverse Hölder inequality.